2D Platformer Game Prototype on Indonesian History Using Scratch - Yuma Akbar; Mohammad Farroos Al Ammaar (Lembaga Komunitas Informasi Teknologi Aceh (KITA), 2024)
In this study, we would like to share a prototype of a 2D platformer game in Scratch centered on the development of Indonesian history that can increase students' interest and motivation in learning history. In search of a more entertaining and successful alternative to the bad lecture situation, the demand for interactive learning media. Visual programming is chosen with Scratch because it is easier to create educational games in this language. Its creation involves the implementation of visual components such as characters, background environments, UI, etc. Data Evaluation provides a positive level of acceptance to students with an average student evaluation score of 4.1/5 Positive responses were obtained for game elements, story content, and ease of operation First, the results of the evaluation of the Validation of 2D Platformer Games in Indonesian History as a Learning Tool. Through student activeness, a more active way of responding to historical material is being implemented by use. Game development has the ability to become a new educational media if it is well structured and organized.